Transcriptome Analysis Identified Gene Regulation Networks in Soybean Leaves Perturbed by the Coronatine Toxin - Zhang, Xiong; He, Bin; Sun, Sheng; Zhang, Zhipeng; Li, Tian; Wang, Hehe; Liu, Zhicheng; Afzal, Ahmed Jawaad; Geng, Xueqing (Frontiers in Sustainable Food Systems, 2021)
The non-host specific Pseudomonas syringae phytotoxin Coronatine (COR) causes chlorosis and promotes toxicity by inducing physiological changes in plants. We performed transcriptome analysis to better understand plants' transcriptional and metabolic response to COR. Toward this end, mock-treated and COR-treated soybean plants were analyzed by RNA-Seq. A total of 4,545 genes were differentially expressed between the two treatments, of which 2,170 were up-regulated whereas 2,375 were down-regulated in COR treated samples. Gene annotation and pathway analysis conducted using the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) databases revealed that the differential genes were involved in photosynthesis, jasmonic acid (JA) synthesis, signal transduction, and phenylpropane metabolism. This study will provide new insights into COR mediated responses and extend our understanding of COR function in plants.